Eksistensi Keluarga Lansia: Studi Implementasi Program Bina Keluarga Lansia Berdasarkan 7 Dimensi Lansia Kecamatan Kediri Lombok Barat - Bagas, Muh Ali (BKI IAIN Pontianak, 2024)
This research aims to explore existence family elderly: study implementation Elderly family development program based on 7 dimensions of elderly in Kediri District, West Lombok. This research​ is filed research that is qualitative in nature with qualitative descriptive approach and deep narrative qualitative strategies business to investigate and tell related stories the experience of the research object is told returned by the researcher in narrative form. Research data obtained through technique interview in-depth, participant observation, and documentation . Whereas For test validity of research data using source triangulation, technique triangulation, and time triangulation. A data analysis study use Creswell data analysis model, namely; analysis spiral, which has 7 stages. Results study show that; The existence of elderly families To be a companion and to care for the elderly is very much needed, both in accompanying the elderly to solve their problems and caring for the elderly who experience a decline in their health , due to that there is four problem And four factor supporters, as well One factor inhibitors found​ in study This. Whereas related with implementation of development programs family elderly show that this program make family elderly in Kediri sub-district have provided attention and helped the elderly in overcoming the problems experienced in their old age so that objective from the creation of the objectives of the elderly family development program, namely to produce resilient elderly people own in accordance with the 7 dimensions of resilient elderly that have been determined by the BKKBN.